The Maintenance of Bagongan Language in Yogyakarta Palace - Sulistyawati Sulistyawati; Emzir Emzir; Sabarti Akhadiah (Future Science, 2021)
The topic of this research is the maintenance of Bagongan Language in Yogyakarta Palace. The objective of this research is to know the use of the Bagongan language in the Yogyakarta palace, especially as a working language of abdi dalem. Bagongan language is known as the language for every abdi dalem in the Yogyakarta Palace. The research uses qualitative approach with ethography method. The ethnographic research procedure in this study are 1) define sub focus, 2) observation and interview, 3) collect data, 4) make notes, 5), analyze data, and 6) make ethnographic reports. The result is (1) Bagongan language is used in the realm of formal office work and correspondence as well as in cultural customs; (2) Internal threatening factors for Bagongan language, namely the weakening of language transmission to the younger generation and externally the situation of bilingualism in the palace; (3) Efforts to preserve the Bagongan language include fostering a sense of pride in the abdi dalem, language transmission to the younger generation, Bagongan language festivals, held a Pawiyatan course for abdi dalem. The Bagongan language needs to be maintained because this language is no longer used in all domains of use in the palace. The Bagongan language is only used in correspondence and traditional palace cultural events.